2015
DOI: 10.1177/0300060515594192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Chinese adjective descriptors of personality and emotional symptoms in young Chinese patients with bipolar disorders

Abstract: Four out of five Chinese personality traits were associated with emotional symptoms in patients with bipolar I or II disorder, but displayed different associations depending on disorder type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(94 reference statements)
4
1
0
Order By: Relevance
“…We also found that patients with BD I and BD II scored significantly higher than the healthy volunteers, while patients with BD I scored higher on HCL-32 than those with BD II. These outcomes are consistent with previous findings [4244] and support the suggestion that BD I and BD II represent manic and depressive extremes in the bipolar spectrum respectively [45]. Moreover, we found that ES2 latency was reduced under Erotica in the BD I group, ES2 latencies were prolonged under Disgust and Happiness, and ES2 durations were reduced under Disgust, Happiness and Sadness in the BD II group.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that patients with BD I and BD II scored significantly higher than the healthy volunteers, while patients with BD I scored higher on HCL-32 than those with BD II. These outcomes are consistent with previous findings [4244] and support the suggestion that BD I and BD II represent manic and depressive extremes in the bipolar spectrum respectively [45]. Moreover, we found that ES2 latency was reduced under Erotica in the BD I group, ES2 latencies were prolonged under Disgust and Happiness, and ES2 durations were reduced under Disgust, Happiness and Sadness in the BD II group.…”
Section: Discussionsupporting
confidence: 93%
“…Participants were asked to complete the rating items using the Likert type scales: 1-very unlike me, 2-moderately unlike me, 3-somewhat like and unlike me, 4-moderately like me, and 5-very like me. The internal alphas of each CADP factor in the two groups were satisfactory (Table 1) as demonstrated previously [6, 7]. …”
Section: Methodssupporting
confidence: 84%
“…Since its development is based on the Chinese culture, CADP might be more suitable to measure the personality-related psychiatric disorders in China. Recently, it has been demonstrated that the CADP traits were correlated respectively with the clinical symptoms of two types of bipolar disorder in Chinese culture [7]. …”
Section: Introductionmentioning
confidence: 99%
“…In our study, BD II patients scored significantly higher on PVP than BD I patients and controls did, BD I patients scored significantly higher on MDQ than both BD II patients and controls did, and both BD I and BD II patients scored significantly higher on HCL-32 than controls did. These results were consistent with previous findings (Xu et al, 2015; Yao et al, 2015; Yu et al, 2015) and supported that BD I and BD II represent manic and depressive extremes in the bipolar spectrum, respectively (Judd et al, 2003). The mean nightmare frequencies were not different between the three groups of participants.…”
Section: Discussionsupporting
confidence: 93%